PERANCANGAN DAN ANALISIS DAYA PENGGERAK DAN TRANSMISI MESIN PENCETAK PAKAN TERNAK DENGAN KONSEP TWO IN ONE - Dede Ardi Rajab; Ridwan Sidik; Ghany Heryana (Sekolah Tinggi Teknologi Wastukancana, 2021)
Abstract.The rapid development of science and technology in the world so that it can bring up ideas, one of which is to make an animal feed printing machine with the Two In One concept to make it more efficient, especially for micro-scale chicken farm entrepreneurs. In making this animal feed printing machine, it cannot be separated from the power of the driving motor, because the power of this motor determines whether or not a movement mechanism occurs in this machine. the force that occurs in this animal feed printing machine, the transmission used must also have its own advantages. This feed printing machine uses an AC induction motor with 1 phase induction, 1 HP power, and a rotation speed of 1490 RPM. The transmission used in this machine has two types of transmission, namely the chain sprocket with a sprocket diameter of 101.6 mm in the gearbox, the diameter of the sprocket on the printer is 100 mm while the diameter of the pully used in the printer is 101.6 mm in diameter and 304.8 mm in the printer. mixer. Loading affects the speed and power that occurs in this machine, when the engine is loaded, the power that occurs is greater and when the engine is loaded the engine rotation speed decreases it causes the load and speed values ​​to be inversely proportional. Keywords: Motor Drive, Transmission, Power